Water Stability Characteristic of Nile Tilapia (Oreochromis niloticus) Feed Coated with Tapioca Flour-beeswax-based Edible Coating - Maharsih, Inggit Kresna; Tarmidzi, Fadhil Muhammad; Pusfitasari, Memik Dian; Alviany, Riza; Yuli, Ahmad; Asnawi, Asnawi (Indonesian Journal of Chemical Research, 2023)
One of the reasons in increasing water turbidity in nile tilapia aquaculture is the presence of spoilage in fish feed that is easily disintegrate and decompose as organic matters in the water. Therefore, a thin layer or edible coating is needed to coat the tilapia feed to slow down the decomposition of the feed due to water absorption. The main ingredients for tilapia feed are tapioca flour added with beeswax solution and glycerol as a plasticizer. In this study, the glycerol concentrations used were 3%, 5%, and 7%, and the beeswax concentrations used were 0.25% w/v, 0.50 % w/v, and 0.75 % w/v. The purpose of this study was analysed the effect of plasticizers and beeswax on the characteristics of the edible coating. The method used to coat tilapia feed is the dipping method, where the product is dipped in a coating solution. The results of the research can be demonstrated by performing a and functional group test using FTIR spectra, contact angle test, and water resistance test of coated fish feed.